Pengaruh motivasi belajar terhadap prestasi belajar santri di Pondok Pesantren - Ridwansyah Ridwansyah; Diana Mutiah (‎‎‎TAZKIYA Journal of Psychology, 2015)
The purpose of this study was in order to know the effect of learning motivation in Islamic boarding school towards achievement of the student. This research sample was 134 students of Daar el-Qolam Islamic boarding school. Sampling technique that used in this research is nonprobability sampling. Multiple Regression Analysis was used for analysis with 0.05 significant. Result showed that there was a significant effect between learning motivation in school, level of the class, previous school, and gender towards achievement in Daar el-Qolam Islamic boarding school. Then, if we see from the coeficient regression of each independent variable, it’s known that there was a significant effect towards achievement, that is default motivation (DEF). Proportions of the variances from all the independent variable toward achievement was 14,4%, whereas the rest was effected by other variable outside this study by 85,6%. Future study is recommended to do research about this other variable DOI: 10.15408/tazkiya.v20i2.9163